Students’ View on Using Online Application to Work on Online Assignment - Nuraeni Nuraeni; Ita Suryaningsih; Sitti Aisyah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2021)
This research aimed to examine students’ views on using online applications, particularly Edmodo to do online assignments (e-assignment). This study was conducted at Universitas Muslim Maros in the English language education department. Eight students joined as the participants voluntarily. This research used qualitative research with a semi-structured interview method. Data were recorded then transcribed. The data then were analyzed using thematic analysis. The result showed that most participants were engaged to work on their assignments online. Positive views were given by the participants as they gained effective learning through the online assignment. However, some students felt the pressure when doing online learning. The big problems are a low internet connection and the use of timer features.